2011
DOI: 10.1007/s12519-011-0257-9
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of iron deficiency and lead exposure on blood lead levels in children

Abstract: Iron deficiency in combination with lead exposure synergistically elevates blood lead levels and susceptibility to its harmful effects in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Anemia, specially iron deficiency anemia affects cognitive performances [8] and school performances in children [911]. It is also suggested that anemia increases the heavy metal absorption in children [12]. It affects the exercise tolerance [13] and hormonal regulation in adults [14].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia, specially iron deficiency anemia affects cognitive performances [8] and school performances in children [911]. It is also suggested that anemia increases the heavy metal absorption in children [12]. It affects the exercise tolerance [13] and hormonal regulation in adults [14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature in the HUE group of natural zeolites (e. g., heulandite and clinoptilolite), samples with Si/Al ratios higher than four belongs to the clinoptilolite type and those with lower ratios (Si/Al < 4) are heulandite type (15).…”
Section: Discussionmentioning
confidence: 99%
“…Following our previous research on adsorption of lead in natural zeolites (15,17), this study was therefore conducted to determine whether intake of this compound possesses protective effects on the learning and memory deficiency induced by lead exposure in rats.…”
Section: Objectivesmentioning
confidence: 99%
See 2 more Smart Citations